1998
DOI: 10.1074/jbc.273.33.20810
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific Binding of Ku Autoantigen to Single-stranded DNA

Abstract: Glucocorticoid-induced transcription of mouse mammary tumor virus is repressed by Ku antigen/DNA-dependent protein kinase (DNA-PK) through a DNA sequence element (NRE1) in the viral long terminal repeat. Nuclear factors binding to the separated single strands of NRE1 have been identified that may also be important for transcriptional regulation through this element. We report the separation of the upper-stranded NRE1 binding activity in Jurkat T cell nuclear extracts into two components. One component was iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 88 publications
2
22
0
Order By: Relevance
“…Recently, the sequence-specific binding of Ku autoantigen to the single, upper strand of NRE1 was shown to be mediated by both Ku subunits (Torrance et al, 1998). The binding of Ku to double-stranded NRE1, however, although it also requires the two subunits, occurs in a two-step manner.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the sequence-specific binding of Ku autoantigen to the single, upper strand of NRE1 was shown to be mediated by both Ku subunits (Torrance et al, 1998). The binding of Ku to double-stranded NRE1, however, although it also requires the two subunits, occurs in a two-step manner.…”
Section: Discussionmentioning
confidence: 99%
“…Repression was also absent from cells containing inactivating mutations in the Ku80 Ϫ/Ϫ subunit but was recovered upon replenishment of Ku80 (30). Subsequently, we have reported that Ku also binds to the upper, single strand of NRE1 (upNRE1) in the MMTV LTR (78), which suggested that the effects of Ku-DNA-PK cs at NRE1 may also involve the Ku-mediated induction of a structural transition in the DNA.…”
mentioning
confidence: 91%
“…Gel slices including the Ku-DNA complexes were then excised from the gel, washed for 10 min three times in SDS sample buffer, heated to 95°C for 5 min, inserted into the wells of SDS-15% polyacrylamide gels, and electrophoresed to separate the cross-linked products. Both protocols are modifications of procedures reported previously (31,78). In the protease experiments, the control undigested samples were also cross-linked in the gel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to DNA ends, Ku is capable of binding artificial DNA structures containing single-to double-strand transitions (15,18). There are also certain sequences that appear to function as entry sites for Ku in double-stranded DNA (19).…”
mentioning
confidence: 99%